VALIDATION OF PARENTAL COMMUNICATION TYPE SCALE FOR ABUSIVE PARENT - Dewi Eko Wati; Riana Mashar (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2021)
Effective communication becomes an important part in developing a child’s character and to prevent the violence of parents towards children. This research aims to develop a communication instrument of parents towards children. There are two communication aspects, which are the opened communication aspect and the closed communication aspect. There are two stages in developing this instrument: first, an introductory study stage to determine the prototype instrument and the second, expert validation examination stage and field examination. Based on the expert analysis results, the instrument has passed the construct validity and it is declared as fit for use. The results of the field examination show that from 34 items, 24 are declared as valid, with the validity value of ≥0.3 and they are reliable as the r value= 0.84≥0.7. From the expert analysis and the field examination, it is concluded that the instrument is fit for research use.